KONSTRUKSI HUKUM PENYELESAIAN SENGKETA PERTANAHAN ATAS TANAH EKS EIGENDOM YANG BELUM DIDAFTARKAN NAMUN TELAH DIKUASAI PIHAK LAIN - Aman, Rifai s.; Candra, Mardi; Tondy, Cicilia Julyani (SENTRI: Jurnal Riset Ilmiah, 2024)
The increasing demand for land due to population growth gave rise to a focus on agrarian law. The pre-1960 dualism of land law (Western land and customary law) ended with the agrarian Basic Law (UUPA) of 1960, which unified land regulation. The UUPA aims to simplify land law for the benefit of the people. The conversion of eigendom rights is regulated by the UUPA, but the settlement of land disputes, although it can be done through non-litigation channels, often leads to litigation, especially in complex cases such as eigendom rights, conversion, and land ownership. This study raises two problems, namely the legal consequences of the former Eigendom land that has not been registered but has been controlled by other parties and the legal construction of Land Dispute Resolution on the Land of the former Eigendom that has not been registered but has been controlled by other parties.This research is normative legal research, with legislation and case approach. The technique of collecting legal materials used by the authors in this study is to collect data by reading and reviewing some literature. The result of this study is that Article 24 of Government Regulation No. 24 of 1997 on land registration provides legal consequences for owners of eigendom deeds who have not registered their land, triggering disputes with communities who have controlled the land. To minimize disputes, it is necessary to establish an alternative institution for resolving land disputes in Indonesia, such as the ex-Eigendom land examination Institute